IMPLEMENTASI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA MATERI PECAHAN: STUDI KASUS DI KELAS V SEKOLAH DASAR NEGERI 2 PARAKAN - Bustomi, Aura Maria; Ejen Jenal Mutaqin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the need for more meaningful mathematics learning in elementary schools, particularly in fraction topics which are often perceived by students as difficult and abstract. The limited use of approaches that connect mathematical content to real-life contexts has contributed to students’ low conceptual understanding and problem-solving abilities. This study aims to describe the implementation of the Realistic Mathematics Education (RME) approach in teaching fractions and to examine its role in supporting the understanding of fifth-grade elementary school students. This research employs a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and supporting documentation. Furthermore, the data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of RME through contextual problems, guided reinvention processes, and active interaction can improve students’ understanding of fraction concepts. Students become more engaged, actively participate in learning, and are able to relate mathematical concepts to real-life situations. Thus, the RME approach can serve as an effective alternative in creating meaningful learning and enhancing students’ conceptual understanding of fractions in elementary school.